Deusa do amor e legisladora ateniense: o duplo protagonismo de Afrodite em Hipólito, de Eurípides - Medeiros, Hamilton Sérgio Nery de (2023)
Hippolytus, by Euripides, is a play first performed in 428 BC during the Peloponnesian War, in which the author presents the story of the young Hippolytus, the fruit of the relationship between the epic hero Theseus and the queen of the Amazons, Hippolyta. In the plot, the young man chooses to chart his own destiny and departs from divine design and tradition in terms of the laws of the oikos and the polis. When Hippolytus comes of age, he decides to remain under the dominion of Artemis and the virginal sphere of the goddess. With this, he withdraws from social life and refuses the institution of marriage, under the legislation of Aphrodite. The goddess, in turn, appears in the plot in her terrible face to those who despise her, and acts as legislator to punish Hippolytus for having strayed from her designs. The aim of this dissertation is to analyze the dual role played by the goddess in Euripides' plot, using excerpts from the play Hippolytus as a corpus, the prologue being the main one. The work is based on theorists such as Florenzano (1996), Romilly (1998), Mossé (2008), the philosophers Plato and Aristotle, literary sources such as Homer and Hesiod, as well as elements of material culture, with photographs of Greek artifacts found in Tarento (Italy).